PENGEMBANGAN MODUL BIMBINGAN KARIER TERHADAP KEMATANGAN KARIER SISWA KELAS XII SMKN 1 CIHAMPELAS - Nurfauziah, Ula; Fatimah, Siti; Pahlevi, Reza (IKIP Siliwangi, 2023)
Modules are teaching materials with a clear and systematic series of activities and learning objectives, thus enabling students to be able to study independently. Career maturity is a person's success in completing typical career development tasks at a certain stage of development. The purpose of this study was to determine the product development process, determine the feasibility of the product according to experts and practitioners, student responses,and the effectiveness of the group guidance module on career maturity. The research method used is research and development (R&D) which was developed by the Borg and Gall model which was adopted by Sugiyono. The results show that the products that need to be developed in schools are group guidance modules on career maturity, product feasibility according to media expertsaat a percentage of 100%, material experts at a percentage of 99.1%, guidance and counseling practitioners at a percentage of 100%, with a very feasible category. Student responses from the model trial involving 12 people got a score of 86.8%, and the assessment of the results of the usage trial involving 38 people got a score of 81% with a very decent category. The effectiveness of the group guidance module on career maturity after conducting the pre-test and post-test showed an increase in the assessment of 10.3%. The results showed that the development of the group guidance module on career maturity has very high category feasibility and can be used as a medium in career guidance services in schools.